Enhancing Value by Continuously Improving Enterprise Culture. (November 2021) - Fisher, Nicholas I.; Lunn, Peter D.; Sasse, Stephen M.
An invaluable feature of the approach developed by AT&T to providing superior value to their customers has been the best-practice process that drove the cycle of continuous improvement, based on the concept of a value tree. This process has since lent itself readily to the task of creating superior value for other stakeholders. Culture and its various categories such as safety culture or risk culture are key drivers of value for several different stakeholder groups. The purpose of this article is to show how the same stakeholder value management process, with a judicious adaptation of a value tree, works well when applied to the task of managing culture, and so opens up new pathways for managers to explore in the endless pursuit of business improvement. A comparative analysis demonstrates how it improves on other current methods in widespread use, in particular avoiding a shortcoming in the wide range of methods deriving from the Safety Awareness Questionnaire.